PENILAIAN POTENSI OBYEK DAYA TARIK WISATA ALAM (ODTWA) KAWASAN MANGROVE SETAPUK DI KELURAHAN SETAPUK BESAR KECAMATAN SINGKAWANG UTARA KOTA SINGKAWANG - Siahaan, Rano Karno; Rifanjani, Slamet; Siahaan, Sarma (Universitas Tanjungpura, 2018)
Singkawang is one of cities in Kalimantan Barat province which is famous for its tourism, ranging from coastal, lake, river, religion, culture and mountains tourism. One of the tourist attraction in Singkawang City is Mangrove Setapuk Area located in Setapuk Besar, Singkawang Utara. This tourist attraction has not been as popular as other tourism because has not been exposed out. This research is expected to promote Mangrove Setapuk Area more widey. It needs to be researched to assess the potential feasibility of developing the object of natural tourist attraction (ODTWA) Mangrove Setapuk area. The method used is accidental sampling. Sampling using Slovia formula to determine the number of respondents. The result from this research, Mangrove Setapuk area get a value of 3765,4 with an average value of 342 (B) is quite potential to be developed. Keyword : Accidental Sampling, Area of Mangrove Setapuk, Potential of Natural Tourist Attraction Object (ODTWA) Potential.